The Effect Of Special Allocation Funds, Profit Sharing Funds And Rest Of Budget Calculations On Capital Expenditures In District And City Governments In West Sumatra Province - Febryandhie Ananda; Dewi Hariani (Universitas Dharma Andalas, 2022)
ABSTRACT The purpose of the study was to determine the effect of special allocation funds, profit-sharing funds and the remainder of the budget calculation on capital expenditures (study on Regency and City Governments in West Sumatra Province). This type of research is quantitative research. The scale used is the ratio measurement scale. The data used is time series data analysis. Source of data in the form of secondary data. The population is 19 regencies and cities in West Sumatra Province, which consists of 12 regencies and 7 cities for the 2014-2019 period. The sampling technique used was saturated sampling. Data collection technique is documentation. The data analysis technique is multiple linear regression analysis. Based on the results of the research that has been done, it can be concluded that the DAK has a significant positive effect on capital expenditures so that the hypothesis is accepted. DBH has a significant positive effect on capital expenditure so that the hypothesis is accepted. SILPA has no significant effect on capital expenditure so that hypothesis is rejected. DAK, DBH and SILPA together have a significant positive effect on capital expenditures. The adjusted R square value is 0.668, this means 66.8% of capital expenditure in 19 regencies and cities in West Sumatra Province which can be explained by special allocation funds (DAK), profit sharing funds (DBH) and excess budget calculations (SILPA). ) while the remaining 33.2% is explained by other factors not examined in this study.